Peningkatan Minat Beli Melalui Pendekatan Strategi Bisnis Dan Kinerja Bisnis UMKM Barokah Chicken Bogor - Dede Nurjannah; Lucky Hikmat Maulana; Hendri Maulana (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research is entitled increasing buying interest through a business strategy approach and business performance in MSME businesses with a case study of Barokah Chicken Broiler Chicken in Kencana Tanah Sareal, Bogor City, with a sample size of 81 respondents. The method used is a questionnaire research instrument which is distributed to customers of Ayam Barokah broiler chicken which is processed using a computer application. The research design used was quantitative with descriptive and verification. The location of this research was carried out at the Barokah Kencana Tanah Sareal Chicken Shophouse, Bogor City. The variables Business Strategy (X1) Business Performance (X2) influence purchasing interest (Y) from the customer side of Ayam Barokah broiler chicken.